Protein modification responds to exercise intensity and antioxidant supplementation - Lamprecht, M.; Oettl, K.; Schwaberger, G.; Hofmann, P.; Greilberger, J. F. (Medicine & Science in Sports & Exercise, 2009)
Purpose: To assess the effects of different exercise intensities and antioxidant supplementation on plasma protein modification.